Discovery and development of steroidal enzyme inhibitors as anti-cancer drugs: state-of-the-art and future perspectives - Bruno Cerra; Antimo Gioiello (Journal of Enzyme Inhibition and Medicinal Chemistry)
Steroidal compounds have emerged as effective therapeutic agents in oncology. Beyond natural-occurring and synthetic steroids that act as cytotoxic anti-tumoral agents, steroidal derivatives can be designed to mime the endogenous substrates of key metabolic enzymes in steroidogenesis, thus reducing the circulating levels of relevant oestrogenic and androgenic hormones responsible for cancer survival and proliferation. Therefore, enzyme inhibition represents an intriguing endocrine approach for the treatment of hormone-dependent tumours, such as breast and prostate cancer, with well-known approved drugs and several pre-clinical and clinical candidates under investigation. This review summarises the key advancements over the past decade (2014–2024) in the development of steroidal enzyme inhibitors endowed with anticancer activity, illustrating their mechanisms of action, therapeutic potential, drug design approaches, and current clinical applications. Furthermore, we discuss challenges related to drug resistance, off-target effects, and future strategies to optimise their efficacy in oncology.